Effect of sodium-glucose co-transporter 2 inhibitor on contrast-induced acute kidney injury and prognosis in type 2 diabetes patients undergoing percutaneous coronary intervention - Yang, Shicheng; Hao, Huifang; Zhai, Xiufeng; Zhang, Peng; Fu, Naikuan (Frontiers in Medicine, 2025)
IntroductionContrast-induced acute kidney injury (CIAKI) is a common and serious complication following contrast administration in patients undergoing percutaneous coronary intervention (PCI). dapagliflozin, a sodium-glucose co-transporter 2 inhibitor (SGLT2i), has demonstrated renal protective effects in various clinical settings. However, the impact of dapagliflozin on the incidence of CIAKI in patients with type 2 diabetes mellitus (T2DM) undergoing PCI is not yet fully understood.ObjectiveTo evaluate the impact of dapagliflozin on CIAKI and long-term prognosis in T2DM patients undergoing PCI.MethodsThis retrospective cohort study included T2DM patients who underwent PCI at the Department of Cardiology, Tianjin University Chest Hospital, from January 2022 to June 2023. Patients were grouped based on dapagliflozin use (dapagliflozin vs. no dapagliflozin). Renal function was assessed before PCI, 48 h, and 1 week post-PCI, measuring serum creatinine, estimated glomerular filtration rate, cystatin C, and neutrophil gelatinase-associated lipocalin. All patients were followed for at least 1 year. The primary endpoint was CIAKI incidence, with secondary endpoints including renal function changes and major adverse cardiovascular events (MACE).ResultsCIAKI occurred less frequently in the dapagliflozin group compared to the control group (5.8% vs. 11.7%, χ2 = 4.494, p = 0.033). After adjusting for confounders, dapagliflozin was an independent predictor of reduced CIAKI risk (OR = 0.365, 95% CI: 0.176–0.767, p = 0.008). During a median 15-month follow-up, the dapagliflozin group had a lower incidence of MACE compared to the control group (Log-rank χ2 = 6.719, p = 0.009). Cox regression analysis showed that dapagliflozin reduced the risk of MACE (HR = 0.484, 95% CI: 0.246–0.955, p = 0.036).ConclusionChronic administration of dapagliflozin can reduces the risk of CIAKI and improves long-term cardiovascular outcomes in T2DM patients undergoing PCI. These findings support its potential use as adjunctive therapy to mitigate kidney injury and improve prognosis in this high-risk population.